Persons, Bodily Awareness and Personal Identity in Kant - Rodríguez Hernández, Montserrat (Con-Textos Kantianos. International Journal of Philosophy, 2023)
In this paper, I will explore a concept of person in Kant based on two features: the unity of consciousness and the consciousness of the numerical identity of one's body in time. The reason for choosing these features is that I take as my starting point the notion of personhood from rational psychology that appears in the major premise of the third paralogism (A361). I will focus on the second feature in order to show that since Kant it is possible to think of the body not merely as an object, but as a subject, i.e., that bodily awareness is self-awareness. I will explain this on the basis of what I will denominate the thesis of corporeality. To develop this thesis, I will draw on passages from Kant's work and contemporary considerations of bodily awareness, specifically the immunity to error through misidentification.